Release type bearing structure and copper foil composite structure
By using a release load bearing structure with a high proportion of organic release layers in the copper foil manufacturing process, the problem of copper foil being easily damaged during tearing or peeling is solved, and the easy separation of copper foil and release layer is achieved, reducing the risk of damage.
Patent Information
- Application Number
- CN202311355897.5
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Priority Date
- 2023-09-20
- Filing Date
- 2023-10-19
- Publication Date
- 2025-03-21
AI Technical Summary
When manufacturing thin or ultra-thin copper foil, the bonding force between the copper foil and the load-bearing structure is too large, resulting in greater force being required during the tearing or peeling process, which can easily cause damage, wrinkles or traces of the copper foil.
A release bearing structure including an organic release layer is adopted, and the weight ratio of the organic matter in the second release layer is greater than the weight ratio of the organic matter in the first release layer. This structure enables the copper foil to be easily separated from the corresponding organic release layer.
The copper foil is easily separated from the release layer, reducing damage to the copper foil during the separation process, and avoiding damage, wrinkles and traces caused by uneven stress.
Smart Images

Figure CN119676966A_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to a release bearing structure and a copper foil composite structure, and in particular to a release bearing structure and a copper foil composite structure comprising an organic release layer. Background Art
[0002] The manufacturing method of the copper foil is generally to form a corresponding copper foil on a corresponding supporting structure, and then remove or separate the copper foil formed on the supporting structure by tearing or peeling.
[0003] As electronic devices become smaller, thin copper foils with a thickness of about 10 micrometers (μm) or even thinner are often used in the manufacture of micro or thin printed circuit boards. However, during the manufacture of thin copper foils or ultra-thin copper foils (especially the aforementioned removal or separation method by tearing or peeling), if the bonding force between the copper foil and the supporting structure is too large, it often requires a large force to tear or peel. However, if the force is large or uneven, the copper foil will often be damaged, wrinkled or have lines.
[0004] Therefore, it is a research topic to improve the quality of copper foil by improving the bearing structure. Summary of the invention
[0005] The present invention is directed to a release bearing structure and a copper foil composite structure comprising the same, which can make the copper foil easily separated from the corresponding release layer.
[0006] According to an embodiment of the present invention, the release bearing structure comprises a bearing layer, a first release layer and a second release layer. The weight proportion of organic matter in the second release layer is greater than the weight proportion of organic matter in the first release layer.
[0007] According to an embodiment of the present invention, a copper foil composite structure comprises a release bearing structure according to an embodiment of the present invention and a copper foil, wherein the copper foil is located on the second release layer of the bearing structure.
[0008] Based on the above, the release bearing structure of the present invention and the copper foil composite structure including the same can make the copper foil easily separated from the corresponding organic release layer (eg, the second release layer). BRIEF DESCRIPTION OF THE DRAWINGS
[0009] Figure 1 It is a cross-sectional schematic diagram of a release bearing structure according to an embodiment of the present invention.
[0010] Figure 2 It is a cross-sectional schematic diagram of a copper foil composite structure according to an embodiment of the present invention.
[0011] Figure 3It is a cross-sectional schematic diagram of a schematic application method of a copper foil composite structure according to an embodiment of the present invention.
[0012] Figure 4 It is a cross-sectional schematic diagram of a copper foil composite structure according to a comparative example of the present invention.
[0013] Description of Reference Numerals
[0014] 100, 100c: release bearing structure;
[0015] 200, 200c: copper foil composite structure;
[0016] 280, 280c: copper foil;
[0017] 120: second release layer;
[0018] 110: first release layer;
[0019] 110c: release layer;
[0020] 170, 170c: bearing layer. DETAILED DESCRIPTION
[0021] Reference will now be made in detail to exemplary embodiments of the present invention, examples of which are illustrated in the accompanying drawings. Whenever possible, the same reference numerals are used in the drawings and the description to refer to the same or like parts.
[0022] In the following detailed description, for the purpose of illustration and not limitation, exemplary embodiments that disclose specific details are set forth to provide a thorough understanding of the various principles of the present invention. However, it will be apparent to one of ordinary skill in the art that, with the benefit of this disclosure, the present invention may be practiced in other embodiments that depart from the specific details disclosed herein. In addition, descriptions of well-known devices, methods, and materials may be omitted to avoid obscuring the description of the various principles of the present invention.
[0023] Ranges may be expressed herein as from "about" one particular value to "about" another particular value, which may also be expressed directly as one particular value and / or to another particular value. When expressing the range, another embodiment includes from the one particular value and / or to another particular value. Similarly, when a value is expressed as an approximation via the use of the antecedent "about," it will be understood that the particular value forms another embodiment. It will be further understood that the endpoints of each range may be clearly related to or independent of the other endpoint.
[0024] In this document, non-limiting terms (such as: may, can, for example or other similar terms) mean that implementation, inclusion, addition or existence are optional or necessary.
[0025] Unless otherwise defined, all terms (including technical and scientific terms) used herein have the same meaning as commonly understood by those of ordinary skill in the art to which the present invention belongs. It will also be understood that terms (such as those defined in commonly used dictionaries) should be interpreted as having a meaning consistent with their meaning in the relevant technical context and should not be interpreted in an idealized or overly formal sense unless explicitly defined as such herein.
[0026] In the drawings, the thickness of some film layers may be exaggerated for clarity.
[0027] Figure 1 It is a cross-sectional schematic diagram of a release bearing structure according to an embodiment of the present invention.
[0028] Please refer to Figure 1 The release bearing structure 100 includes a bearing layer 170 , a first release layer 110 and a second release layer 120 .
[0029] [Bearing layer of release bearing structure]
[0030] The present invention has no particular limitation on the material of the carrier layer 170, as long as the carrier layer 170 is suitable for the film, layer and / or component carried thereon and is suitable for subsequent applications. In one embodiment, the carrier layer 170 may be a sheet, plate or block of metal material. In a preferred embodiment, the carrier layer 170 may be a copper material (e.g., a copper sheet, a copper plate or a copper block), which may be preferred because the copper material may have the same or similar coefficient of thermal expansion (CTE) and / or the same or similar physical or chemical properties as the copper layer (e.g., a copper-plated layer or a copper foil) subsequently formed thereon.
[0031] In one embodiment, the thickness of the carrier layer 170 may be about 18 micrometers (μm) to about 35 μm.
[0032] [First release layer of release bearing structure]
[0033] In one embodiment, the weight ratio of inorganic matter in the first release layer 110 is greater than the weight ratio of inorganic matter in the second release layer 120. In one embodiment, the first release layer 110 can be referred to as an inorganic release layer. In one embodiment, the first release layer 110 substantially contains no organic matter.
[0034] In a preferred embodiment, the first release layer 110 may be formed of inorganic metal salts. The reason for this preference is that, compared with the bonding between the subsequent film layer (e.g., the second release layer 120) formed of organic materials and metal (e.g., copper), the first release layer 110 formed of inorganic metal salts can have better bonding strength with both of the aforementioned two. In other words, the bonding strength between the first release layer 110 and the metal (e.g., copper) carrier layer 170 can be greater than the bonding strength between the film layer (e.g., the second release layer 120) formed of organic materials and metal (e.g., copper), and the bonding strength between the first release layer 110 and the film layer (e.g., the second release layer 120) formed of organic materials can be greater than the bonding strength between the film layer (e.g., the second release layer 120) formed of organic materials and metal (e.g., copper).
[0035] In one embodiment, the first release layer 110 may be formed on the carrier layer 170 by electroplating. The electrolyte used in the electroplating may be an electrolyte compound containing nickel, cobalt, molybdenum, manganese, iron and / or tungsten. For example, it may be a sulfate, nitrate, phosphate, chloride, salt derived from oxides of the metals and / or hydrates of the salts.
[0036] In one embodiment, before forming the first release layer 110 on the carrier layer 170, the carrier layer 170 may be subjected to appropriate pre-treatment. The pre-treatment may include but is not limited to: acid washing, alkali washing, degreasing and / or electrolytic cleaning, so that the carrier layer 170 has a cleaner outer surface and / or an outer surface that is easier for the first release layer 110 to adhere to.
[0037] In one embodiment, the aforementioned nickel-containing compound may include, for example, nickel sulfate, ammonium nickel sulfate, nickel nitrate or nickel chloride.
[0038] In one embodiment, the aforementioned cobalt-containing compound may include, for example, cobalt sulfate, cobalt nitrate, cobalt phosphate, cobalt chloride or cobaltous chloride.
[0039] In one embodiment, the molybdenum-containing compound may include, for example, sodium molybdate, potassium molybdate, molybdenum disulfide, molybdenum nitrate, molybdenum phosphate or molybdenum chloride.
[0040] In one embodiment, the aforementioned manganese-containing compound may include, for example, manganese sulfate, manganese nitrate, manganese phosphate or manganese chloride.
[0041] In one embodiment, the aforementioned iron-containing compound may include, for example, ferric sulfate, ferric nitrate, ferric phosphate or ferric chloride.
[0042] In one embodiment, the aforementioned tungsten-containing compound may include sodium tungstate or potassium tungstate, for example.
[0043] In one embodiment, the solvent of the electrolyte may be water.
[0044] The electrolyte may have a corresponding pH value by adding an acid or an alkali. In one embodiment, the pH value of the electrolyte may be about 2.5 to 4.5. In one embodiment, the added acid may include sulfuric acid, nitric acid, hydrochloric acid or phosphoric acid.
[0045] In one embodiment, the temperature of the electrolysis may be in the range of about 20° C. to 60° C. In one embodiment, the current density of the electrolysis may be about 0.1 A / dm 2 Up to 50A / dm 2 within the range.
[0046] In one embodiment, the concentration of the metal ions to be plated in the electrolyte may be about 0.005M (molar, mol / L) to 0.5M.
[0047] In one embodiment, the conductivity of the electrolyte can be adjusted by adding other non-plated electrolytes. The metal contained in the aforementioned "non-plated electrolyte" is basically not reduced and plated on the carrier layer 170. The aforementioned "non-plated electrolyte" can include, for example, corresponding potassium salts or sodium salts.
[0048] In one embodiment, the electroplating time can be adjusted according to requirements (eg, corresponding thickness) or corresponding conditions (eg, current density, electroplating temperature and / or concentration of metal ions to be plated).
[0049] In one embodiment, the electroplating layer formed on the carrier layer 170 can basically be referred to as the first release layer 110 .
[0050] In one embodiment, after electroplating, it is preferable to appropriately heat the carrier layer 170 and the electroplated layer thereon to form the corresponding first release layer 110. This is preferably because the metal in the first release layer 110 and the metal in the carrier layer 170 may form a corresponding eutectic mixture, thereby improving the bonding force between the first release layer 110 and the carrier layer 170. This is preferably because the outer surface of the first release layer 110 (i.e., the surface that is not in contact with the carrier layer 170 and is exposed to the outside) may be oxidized and / or roughened, thereby improving the bonding force between the first release layer 110 and the second release layer 120 formed subsequently.
[0051] In one embodiment, the thickness of the first release layer 110 may be approximately 10 nanometers (nm) to 1 micrometer (μm); preferably, the thickness may be approximately 50 nanometers to 300 nanometers.
[0052] [Second release layer of release bearing structure]
[0053] After forming the corresponding first release layer 110 on the aforementioned carrier layer 170 , the second release layer 120 may be formed on the first release layer 110 .
[0054] In one embodiment, the weight ratio of organic matter in the second release layer 120 is greater than the weight ratio of organic matter in the first release layer 110. In one embodiment, the weight ratio of inorganic matter in the second release layer 120 is less than the weight ratio of inorganic matter in the first release layer 110. In one embodiment, the second release layer 120 may substantially not include inorganic matter. In one embodiment, the second release layer 120 may be referred to as an organic release layer.
[0055] In one embodiment, the corresponding film-forming composition may be formed on the first release layer 110 by spraying, rolling, dipping, spraying or other suitable methods; then, the film-forming composition on the first release layer 110 may be selectively cured or semi-cured by suitable methods (such as heating and / or standing) to form the corresponding second release layer 120. In one embodiment, the process of forming the corresponding film-forming composition on the second release layer 120 may be performed at an environment of about 15° C. to 70° C.; preferably, it may be performed at an environment of room temperature (about 25° C.) to 70° C.
[0056] In one embodiment, the aforementioned film-forming composition may include an azole compound.
[0057] In one embodiment, the concentration of the azole compound in the film-forming composition may be about 0.1 g / L to about 50 g / L.
[0058] In one embodiment, the aforementioned azole compound may include an imidazole compound, a triazole compound, a tetrazole compound, the aforementioned derivative compounds, or a mixture thereof. The aforementioned "derivative compound" may be a hydrogen atom connected to a carbon atom in an azole ring replaced by an electron-donating group; or, the azole ring is fused / condensed with an aromatic ring. The aforementioned "electron-donating group" may be, for example, a dialkylamino group (-NRR'), an alkylamino group (-NHR), an amino group (-NH2), a hydroxyl group (-OH), an alkoxy group (-OR); preferably, it is a nitrogen-containing electron-donating group; more preferably, it is an amino group. The aforementioned "aromatic ring" may be, for example, a benzene ring or a naphthalene ring; preferably, it is a benzene ring.
[0059] In one embodiment, the film-forming composition can be made alkaline by adding an alkali agent. In one embodiment, the added alkali agent can include sodium hydroxide, potassium hydroxide, or a mixture thereof. In one embodiment, the alkali equivalent of the film-forming composition is approximately equivalent to about 0.1 wt % to about 20 wt % of sodium hydroxide.
[0060] In one embodiment, if the film-forming composition includes an azole compound having a combined / fused azole ring and an aromatic ring, the corresponding conjugate base can be made more stable through the benzene ring in an alkaline environment. In this way, the film-forming composition and / or the corresponding film layer formed can be made more stable. In one embodiment, the azole compound having a combined / fused azole ring and an aromatic ring can be, for example, benzotriazole (CAS: 95-14-7).
[0061] In one embodiment, if the film-forming composition includes an azole compound in which the hydrogen of a carbon atom in an azole ring is replaced by an amino group, it is less likely to form a corresponding ammonium ion (-NH3) in an alkaline environment. +) state. In this way, the film-forming composition and / or the corresponding film layer formed can be made more stable, and / or can have better bonding with the first release layer 110. In one embodiment, the azole compound in which the hydrogen of the carbon atom in the azole ring is replaced by an amino group may include aminotetrazole, aminotriazole or aminodiazole. In one embodiment, the aminotetrazole may include 5-aminotetrazole (5-aminotetrazole, CAS: 4418-61-5) and 1,5-diaminotetrazole (1,5-diaminotetrazole, CAS: 2165-21-1). In one embodiment, the aminodiazole may include 2-amino-1,3,4-thiadiazole (2-amino-1,3,4-thiadiazole, CAS: 4005-51-0). In one embodiment, the aminotriazole may include 3,5-diamino-1,2,4-triazole (3,5-diamino-1,2,4-triazole, CAS: 1455-77-2).
[0062] In one embodiment, the film-forming composition can be a sodium hydroxide aqueous solution including aminotetrazole and benzotriazole, wherein the concentration of aminotetrazole is about 0.1 grams per liter (g / L) to 10 g / L, the concentration of benzotriazole is about 0.1 g / L to 10 g / L, and the concentration of sodium hydroxide is about 0.1 wt% to 5 wt%.
[0063] In one embodiment, the film-forming composition may be a sodium hydroxide aqueous solution including 2-amino-1,3,4-thiadiazole, 3,5-diamino-1,2,4-triazole, and benzotriazole. In one embodiment, in the film-forming composition, the weight concentration ratio of 2-amino-1,3,4-thiadiazole, 3,5-diamino-1,2,4-triazole, and benzotriazole is about 1:1:1 to 1:1:3. In one embodiment, in the film-forming composition, the total weight concentration of 2-amino-1,3,4-thiadiazole, 3,5-diamino-1,2,4-triazole, and benzotriazole is about 0.1 g / L to 10 g / L, and the concentration of sodium hydroxide is about 0.1 wt% to 5 wt%.
[0064] In one embodiment, the thickness of the second release layer 120 may be about 1 nanometer to 100 nanometers, preferably, 1 nanometer to 50 nanometers, and more preferably, 1 nanometer to 20 nanometers.
[0065] [Release bearing structure]
[0066] Please continue to refer to Figure 1 In the release bearing structure 100, the first release layer 110 may be sandwiched between the bearing layer 170 and the second release layer 120. The opposite sides of the first release layer 110 may contact the bearing layer 170 and the second release layer 120, respectively.
[0067] In one embodiment, since the material and the forming method of the first release layer 110 are different from the material and the forming method of the second release layer 120 , the first release layer 110 and the second release layer 120 may have a corresponding contact interface.
[0068] In one embodiment, a corresponding eutectic mixture may be formed at the contact point between the first release layer 110 and the carrier layer 170 .
[0069] [Copper foil composite structure]
[0070] Figure 2 It is a cross-sectional schematic diagram of a copper foil composite structure according to an embodiment of the present invention.
[0071] The copper foil composite structure 200 can be formed by the release supporting structure 100 of the aforementioned embodiment.
[0072] In one embodiment, the corresponding copper foil 280 may be formed on the second release layer 120 by sputtering, electroplating after sputtering, or other suitable or commonly used methods.
[0073] In one embodiment, the copper foil 280 may have a thickness of about 1 micrometer to about 5 micrometers.
[0074] [Application of copper foil composite structure]
[0075] The application of the copper foil composite structure 200 can be appropriately adjusted according to the requirements, and is not limited in the present invention.
[0076] In one embodiment, it is possible to Figure 2 The copper foil composite structure 200 shown in FIG. 1 is appropriately cut.
[0077] In one embodiment, Figure 2 The copper foil composite structure 200 shown in FIG. 1 is appropriately rolled up.
[0078] In one embodiment, Figure 2 The copper foil 280 in the copper foil composite structure 200 shown in FIG. 1 is patterned in an appropriate manner.
[0079] In one embodiment, the Figure 2 On the copper foil 280 in the copper foil composite structure 200 shown in FIG. 1 , other film layers are formed by appropriate means.
[0080] In one embodiment, the Figures 2 to 3 As shown, the copper foil 280 (which may include an unpatterned copper foil or a patterned copper foil) is separated from the second release layer 120 .
[0081] In one embodiment, the copper foil composite structure 200 is heated and pressurized due to the copper foil substrate manufacturing process requirements, which may result in different degrees of peeling force during the separation process of the copper foil 280 and the second release layer 120 .
[0082] The copper foil 280 can be easily separated from the second release layer 120 by the second release layer 120 of an embodiment of the present invention. In this way, the copper foil 280 is less likely to be damaged, wrinkled, or have lines caused by uneven stress during the process of separating the copper foil 280 or after separation.
[0083] [Examples and Comparative Examples]
[0084] The present invention will be specifically described below with reference to Examples and Comparative Examples, but the present invention is not limited to the following Examples at all.
[0085] [Example]
[0086] The copper foil composite structure of [Example] is formed by the above-mentioned embodiment. The copper foil composite structure of [Example] includes a release bearing structure and a copper foil plated thereon. The cross-section of the copper foil composite structure of [Example] can be the same as or similar to Figure 2 That is to say, in the copper foil composite structure of [Example], its release bearing structure can be the same as or similar to the release bearing structure 100 of the aforementioned embodiment. Moreover, the material, thickness or formation method of the copper foil, the second release layer, the first release layer and / or the bearing layer of [Example] can be the same as or similar to the material, thickness or formation method of the copper foil 280, the second release layer 120, the first release layer 110 and / or the bearing layer 170 of the aforementioned embodiment.
[0087] In [Example], the film-forming composition for forming the second release layer is a sodium hydroxide aqueous solution including 2-amino-1,3,4-thiadiazole, 3,5-diamino-1,2,4-triazole, and benzotriazole. The total concentration of 2-amino-1,3,4-thiadiazole, 3,5-diamino-1,2,4-triazole, and benzotriazole is about 0.1 g / L to 10 g / L, and the mixing weight ratio is 1:1:1 to 1:1:3, and the concentration of sodium hydroxide is about 0.1 wt% to 5 wt%.
[0088] [Comparative Example 1]
[0089] The copper foil composite structure of [Comparative Example 1] is similar to the copper foil composite structure of [Example], except that: the copper foil composite structure of [Comparative Example 1] does not have any film layer that is the same as or similar to the second release layer.
[0090] For details, please refer to Figure 4The copper foil composite structure 200c of [Comparative Example 1] includes a release bearing structure 100c and a copper foil 280c plated thereon. The release bearing structure 100c includes a bearing layer 170c and a release layer 110c.
[0091] In the copper foil composite structure 200c of [Comparative Example 1], the material, thickness or formation method of the copper foil 280c, release layer 110c and / or carrier layer 170c can be the same or similar to the material, thickness or formation method of the copper foil, first release layer and / or carrier layer of [Example].
[0092] [Evaluation of Examples and Comparative Example 1]
[0093] The copper foil was peeled off at different temperatures using a common or standard peel test method (such as ASTM D1000, ASTM D3330 or similar). Ten groups of tests were repeated under the same experimental conditions, and the average value (unit: gf / cm) of the minimum peeling force required to peel off the copper foil and the corresponding standard deviation value (unit: gf / cm) were recorded. The test results are listed in [Table 1].
[0094] [Table 1]
[0095]
[0096] In the aforementioned test, an environment at about 390° C. can be used to simulate a temperature range that may be applicable to a flexible PCB manufacturing process, and an environment at about 390° C. can be used to simulate a temperature range that may be applicable to a rigid PCB manufacturing process.
[0097] As shown in [Table 1], compared with [Comparative Example 1], the copper foil of the copper foil composite structure of [Example] can be torn off more easily. Therefore, in many experiments, the copper foil torn off from the copper foil composite structure of [Example] was not damaged, and there were almost no wrinkles or lines caused by uneven stress visible to the naked eye.
[0098] [Comparative Example 2]
[0099] The appearance of the copper foil composite structure of [Comparative Example 2] is substantially the same as that of the copper foil composite structure of [Example], except that the film-forming composition used to form the second release layer is different. Specifically, in [Comparative Example 2], the film-forming composition used to form the second release layer is an aqueous sodium hydroxide solution including benzotriazole. That is, in [Comparative Example 2], the film-forming composition used to form the second release layer does not include other azole compounds (such as aminodiazole, aminotriazole, aminotetrazolyl) other than benzotriazole. Moreover, the concentration of benzotriazole in the film-forming composition in [Comparative Example 2] is substantially the same as the sum of aminotetrazolyl and benzotriazole in the film-forming composition of [Example].
[0100] The peeling force required to peel off the copper foil of the copper foil composite structure of [Comparative Example 2] was greater than the peeling force required to peel off the copper foil of the copper foil composite structure of [Example].
[0101] The peeling force required to peel off the copper foil of the copper foil composite structure of [Comparative Example 2] is slightly smaller than the peeling force required to peel off the copper foil of the copper foil composite structure of [Comparative Example 1].
[0102] In summary, the release bearing structure of an embodiment of the present invention can be used to form a copper foil composite structure of an embodiment of the present invention. Moreover, the copper foil composite structure of an embodiment of the present invention can easily separate the copper foil from the corresponding release layer (eg, the second release layer).
[0103] [Practicality]
[0104] The release bearing structure of an embodiment of the present invention can be suitable for forming a copper foil composite structure of an embodiment of the present invention. The copper foil composite structure of an embodiment of the present invention can be suitable for subsequent processing and can be used as a material for producing electronic products (such as circuit boards).
[0105] Finally, it should be noted that the above embodiments are only used to illustrate the technical solutions of the present invention, rather than to limit it. Although the present invention has been described in detail with reference to the aforementioned embodiments, those skilled in the art should understand that they can still modify the technical solutions described in the aforementioned embodiments, or replace some or all of the technical features therein with equivalents. However, these modifications or replacements do not cause the essence of the corresponding technical solutions to deviate from the scope of the technical solutions of the embodiments of the present invention.
Claims
1. A release bearing structure, characterized in that: include: Bearing layer; A first release layer; as well as A second release layer, wherein the weight ratio of organic matter in the second release layer is greater than the weight ratio of organic matter in the first release layer.
2. The release bearing structure according to claim 1, characterized in that: The second release layer is formed by a film-forming composition, wherein the film-forming composition includes an azole compound.
3. The release bearing structure according to claim 2, characterized in that: In the film-forming composition, the thickness of the second release layer is 1 nanometer to 20 nanometers.
4. The release bearing structure according to claim 2, characterized in that: The azole compounds include azole compounds substituted with electron-donating groups or azole compounds with fused / condensed azole rings and aromatic rings.
5. The release bearing structure according to claim 4, characterized in that: The azole compounds include the azole compounds substituted with electron-donating groups and the azole compounds with fused / condensed azole rings and aromatic rings.
6. The release bearing structure according to claim 2, characterized in that: The azole compound includes a diazole compound, a triazole compound, a tetrazole compound or a mixture thereof.
7. The release bearing structure according to claim 2, characterized in that: The film-forming composition is alkaline.
8. The release bearing structure according to claim 7, characterized in that: The alkali equivalent of the film-forming composition is 0.1 wt % to 20 wt % of sodium hydroxide.
9. The release bearing structure according to claim 1, characterized in that: The first release layer and the second release layer are in contact with each other and have a contact interface therebetween.
10. A copper foil composite structure, characterized in that: include: The release bearing structure according to claim 1; as well as The copper foil is located on the second release layer of the bearing structure.